The Labor Force Absorption Improvement of Micro and Small Enterprises (MSEs) in Indonesia - Eka Miftakhul Jannah; Aditya Arief Rachmadhan; Meidaliyantisyah Meidaliyantisyah; Jekvy Hendra (Universitas Negeri Malang, 2021)
The aims to determine steps to increase the labor force absorption of the Micro and Small Enterprises (MSEs) sector. This research using the structural equation model partial least square (SEM-PLS) method with cross-section secondary data within provinces (34 provinces) from the 2016 Economic Census (2017 census). The analysis results showed that the labor force absorption of MSEs in Indonesia was directly and positively affected by the number of MSEs and the income of MSEs. The number of MSEs in Indonesia was positively affected by the education level of MSEs owners. Meanwhile, the income of MSEs was positively affected by the use of the internet (digital technology) of MSEs. The education level of MSE owners was the only factor that had an indirect positive effect on the labor force absorption of MSEs. Increasing the labor force absorption of MSEs in Indonesia can be promoted by strengthening the entrepreneurship curriculum to foster an entrepreneurial spirit in students, especially at the higher education level, to grow the startup businesses. In addition, digital marketing partnerships with various e-commerce platforms providing marketplaces and online courier service platforms to increase MSEs income are encouraged. Keywords: Entrepreneurship Education, Startup Business, MarketplaceJEL Classification: J23, M20, O17